(untitled) (Swiss Medical Weekly, 2025)
STUDY AIM: Undiagnosed and therefore untreated permanent paediatric hearing loss can have a detrimental impact on a child’s speech, language, social and educational development, and quality of life. Therefore, early diagnosis is required for successful treatment with hearing aids to minimise the negative impact of hearing loss. Newborn hearing screening programmes may have decreased the average age at diagnosis of hearing loss worldwide, but outcomes vary widely between countries. In this study, we therefore aimed to assess the median age of children at diagnosis of permanent unilateral and bilateral hearing loss in Eastern Switzerland. METHODS: In this retrospective cohort study, children born in Eastern Switzerland with permanent hearing loss diagnosed at the Division of Paediatric Audiology at the Cantonal Hospital of St Gallen (the tertiary referral centre for Eastern Switzerland) were included. The study period was from 1 January 2014 to 31 December 2019. The primary endpoint was age at diagnosis of permanent unilateral or bilateral hearing loss. Descriptive data collected were the type and WHO grade of hearing loss, the status of newborn hearing screening and other information such as path of referral and place of residence. RESULTS: In total, 107 children with permanent hearing loss were included in this study. Overall, the median age at diagnosis was 45.0 months (interquartile range [IQR] 5.7–74.8). The median age at diagnosis for children with bilateral hearing loss was 25.8 months (IQR 3.6–70.5), compared to 63.1 months (IQR 11.4–88.5) for children with unilateral hearing loss. For children with bilateral hearing loss, the median age at diagnosis was lower with higher WHO grades of hearing loss: 65.6 months (IQR 11.1–131.6) for grade I vs 4.5 months (IQR 2.2–6.0) for grade IV. Children with bilateral hearing loss and a documented failed newborn hearing screen were diagnosed early: median age at diagnosis 4.0 months (IQR 2.2–12.3). CONCLUSION: In conclusion, the age at diagnosis of paediatric permanent hearing loss in our study is variable and, in some cases, late. This applies particularly to bilateral hearing loss that should have been diagnosed by the newborn hearing screen in congenital cases and unilateral hearing loss.